The role of smoking in the development of strokes at a young age - V. V. Gusev; D. A. Medvedev; O. A. Lvova; N. A. Shamalov; O. P. Kovtun (Klinicist)
Stroke in young patients is a disease based on a number of known specific non-modifiable factors (extracranial artery dissection, thrombophilia, open oval hole, etc.) and modifiable factors (alcohol abuse, drug use, smoking, etc.), in combination leading to the development of pathology. Smoking is a generally recognized modifiable risk factor for stroke, which is directly proportional to the number of tobacco-containing products smoked. Quitting smoking is the basis of prevention, an integral part of the treatment and rehabilitation of stroke patients. If it is impossible to completely give up smoking combustible cigarettes, it is advisable to switch to alternative smokeless products. This article presents the results of current studies on the comparative assessment of the risk of stroke in young people when using combustible cigarettes and smokeless analogues.